HUBUNGAN PENGETAHUAN, POLA KONSUMSI DAN PEMANFAATAN SAYURAN HIJAU TERHADAP ANEMIA PADA IBU HAMIL - Antini, Ari; Trisnawati, Irna (Poltekkes Kemenkes Bandung, 2025)
Anemia is a prevalent health issue in the global population, with approximately 30% being impacted. The main cause of anemia in pregnant women is lack of knowledge. In developing countries, anemia is often caused by a lack of proper nutrition and balanced diet. In Karawang Health Profile from 2018, the Maternal Mortality Rate (MMR) is ranked third at the provincial level, with postpartum hemorrhage and anemia being the primary cause, accounting for 26% of the cases. An initial investigation revealed that 50% of them were anemic, while 60% were unaware of foods rich in iron. This study aimed to assess the connection between knowledge, dietary habits, and the use of green vegetables in anemia among pregnant women. Research methods a cross-sectional design was used. This study was conducted between June and August 2023. The population and sample of pregnant women in the third trimester who met the inclusion criteria included 82 people. Sampling was based on accidental sampling and consumption pattern instruments using the FFQ for knowledge and utilization of green vegetables using interview guidelines. There was no difference in the proportion of anemia between mothers with poor and good knowledge (p= 0.068), in the proportion of anemia between mothers who did not use green vegetables well and green vegetables well (p= 1,000), and in anemia between mothers with poor and good consumption patterns (p= 0.044). It is recommended that health education programs for pregnant women regarding the consumption of high iron be improved.